Effects on Apical Outcomes of Regulatory Relevance of Early‐Life Stage Exposure of Double‐Crested Cormorant Embryos to 4 Environmental Chemicals. (18th December 2020) - Crump, Doug; Boulanger, Emily; Farhat, Amani; Williams, Kim L.; Basu, Niladri; Hecker, Markus; Head, Jessica A.
Abstract: Environmental risk assessment is often challenged by a lack of toxicity data for ecological species. The overall goal of the present study was to employ an avian early‐life stage toxicity test to determine the effects of 4 chemicals (benzo[ a ]pyrene [BaP], chlorpyrifos, fluoxetine hydrochloride [FLX], and ethinyl estradiol [EE2]) on an ecologically relevant avian species, the double‐crested cormorant ( Phalacrocorax auritus ), and to compare our results with those we previously reported for a laboratory model species, Japanese quail. Chemicals were dissolved in dimethyl sulfoxide and administered via air cell injection to fertilized, unincubated double‐crested cormorant eggs at 3 nominal concentrations, the highest selected to approximate the 20% lethal dose. Of the 4 chemicals, only chlorpyrifos and FLX were detected in liver tissue of embryos at midincubation (day 14) and termination (day 26; 1–2 d prior to hatch); EE2 and BaP were not detectable, suggesting embryonic clearance/metabolism. No apical effects were observed in double‐crested cormorant embryos up to the highest concentrations of chlorpyrifos (no‐observed‐effect level [NOEL] = 25 µg/g) or FLX (NOEL = 18 µg/g). Exposure to EE2 reduced embryonic viability and increased deformities at a concentration of 2.3 µg/g (NOEL = 0.18 µg/g), and BaP decreased embryonic viability (median lethal dose = 0.015 µg/g; NOEL = 0.0027 µg/g). Compared with Japanese quail, double‐crested cormorant were more sensitive with regard to embryolethality and deformities for EE2 and embryolethality for BaP, whereas they were less sensitive to embryonic deformities associated with chlorpyrifos exposure. These data reinforce the idea that standardized toxicity tests using a laboratory model species may not always be protective of wild birds, and thus they stress the importance of developing such alternative testing strategies (e.g., the EcoToxChip Project) for ecologically relevant species to augment risk assessment efforts. Environ Toxicol Chem 2021;40:390–401. © 2020 SETAC